Analisis Faktor Rendahnya Penggunaan Kontrasepsi Intra Uterine Device (IUD) di Jawa Timur 2015 - Pratiwi Purbaningrum; Iswari Hariastuti; Arief Wibowo (Universitas Airlangga, 2019)
Intrauterine Device (IUD) is one type of contraceptives that is made from flexible plastic and implanted in the uterus. The IUD is included as a long-term contraception which is very effective in regulating the distance of pregnancy, is reversible, and can be worn by women of all reproductive ages. Therefore, the government is doing all kinds of effort to the number of IUD users. Surprisingly, the number of women using the IUD has kept decreasing every year. This study aims to analyze the factors affecting the low use of IUD contraception in East Java in 2015. The data were obtained from the Mid-term Development Plan Survey in 2015 by taking a sample from all the women who were willing to be interviewed in the Mid-term Development Plan Survey in East Java Province with the following characteristics: being 15–49 years of age, being married, not getting pregnant, and were still using contraceptions. There were 1,220 respondents who could be interviewed. The result of binary regression testing with a significant degree of 5% yielded three significant variables, namely age (P-value = 0.002), education (P-value = 0.000), and birth control service (P-value = 0.000). Healthy women who were around 15–19 years old, had low education, and had limitted access to private birth control services tended to avoid the IUD contraception more. Therefore, it is expected that the government is making cooperation with the related sectors in an attempt to increase the use of IUD contraceptives in the East Java Province in 2015 with more emphases on age, education and birth control service locations.